Factors Influencing Unsafe Work Behavior In Construction Work For The Construction Of The Upt Vertical Hospital In Surabaya By Pt Wijaya Karya, Building Division - Patoni, Umar; Hasibuan, Bernard; Ramli, Soehatman (Jurnal Ekonomi, 2024)
This research has the purpose to determine the influence of knowledge, supervision, facility availability, and management commitment as moderators on unsafe behavior among workers in the Construction Project of UPT Vertical Hospital Surabaya. The research used a Structural Equation Model (SEM) approach with the measurement model using the SmartPLS version 3.2.9 program. The research results indicate that knowledge, supervision, and facilities can influence the unsafe behavior of workers, and management commitment cannot influence knowledge, supervision, and facilities on the unsafe behavior of workers in the construction of the UPT Vertical Surabaya Hospital.